Directorship appointments and firm performance in an emerging economy, Malaysia - Pang, Shwu Fen (Universiti Malaysia Sarawak (UNIMAS), 2013)
The number of directorships that directors can hold has been a contentious corporate governance issue around the world. The issue of multiple directorships and its effects to firm performance as well as value creations are still attracts considerable debate since it brings benefit and disadvantages to firms. This study examines three major parts: (1) The relationship between multiple board appointments and firm performance. (2) The relationship between other governance characteristic and firm performance. (3) The relationship between busy director and attendance of meetings. For the firm performance, we used three types of measurements which are operating margin, Tobin’s Q and market-to-book ratio. We use of a sample of 504 listed firms in Malaysia in 2009 and regression models to investigate the relationship. We found evidence that multiple directorships are positively linked to firm performance in all models. Director with multiple board appointments are able to bring benefit to the firm as they have broad experience, knowledge and skills to monitor the firm. Other than that, we also found that board size is also positively significant in all three models which indicated that larger boards benefit the firm as they provide diversity in terms of experience, skill and helping firms to secure critical resources and contracts. Lastly, we found that the relations between busy director and their attendance of meetings are significantly related at a negative direction. This implies that director with more directorships are likely to be absence in the board meetings. This study clarifies similar results with some prior literature on the impact of multiple directorships.